Benzodiazepines and/or neuroleptics for the treatment of delirium in palliative care?—a critical appraisal of recent randomized controlled trials - Gaertner, Jan; Eychmueller, Steffen; Leyhe, Thomas; Bueche, Daniel; Savaskan, Egemen; Schlögl, Mathias (Annals of Palliative Medicine; Vol 8, No 4 (September 27, 2019): Annals of Palliative Medicine, 2019)
Delirium is a frequent condition in patients in a palliative care situation and most often associated with substantial burden or even danger for the persons concerned as well as caregivers and health-care-professionals. Despite the lack of randomized-controlled-trials (RCTs) benzodiazepines and neuroleptic agents are used extensively in palliative care for the pharmacological management of delirium. A focused review for RCTs assessing pharmacotherapy with benzodiazepines and neuroleptics for the treatment of delirium in patients treated in a palliative care or hospice setting published in 2017 was performed in PubMed. A narrative summary of the findings of the RCTs and practical recommendation are presented. Of 42 publications, two RCTs could be included. One trial assessed the use of lorazepam (in addition to haloperidol) in case of agitation, the other placebo or risperidone or haloperidol in delirious palliative care patients. Neither risperidone nor haloperidol were superior compared to placebo, but were associated with higher mortality and morbidity. Lorazepam (along with haloperidol) reduced agitation in patients with delirium compared to placebo (along with haloperidol), but was unable to reduce the severity and incidence of delirium. It is of importance to note that psychopharmacotherapy with antipsychotics is mainly indicated for the hyperactive form of delirium and psychotic symptoms (e.g., delusions or hallucinations) in the hyper- and hypoactive delirium. Severe agitation and aggressivity can be an indication for neuroleptics, when non-pharmacological interventions fail, whereas the use of benzodiazepines has to be limited to critical situations where neuroleptics cannot be applied and cases of delirium due to alcohol withdrawal. Both substances can aggravate, precipitate or mask delirium, result adverse events with substantial distress or unfavorable survival outcomes for the patients. Thus, they should only be used in severely symptomatic patients and the duration of the medication has to be limited in time. When delirium symptoms decay the psychopharmacotherapy has to be tapered. More important than psychopharmacotherapy, the thorough investigation and treatment of potentially reversible causes of delirium (e.g., pharmacotherapy, infection) and the routine identification of patients at risk for delirium along with prophylactic measures are essential. The recently published landmarks RCTs provide moderate evidence to adopt recommendations from other medical specialties (i.e., intensive care, geriatrics) to the field of palliative care.